2009
DOI: 10.1080/02699050902788428
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of driving ability after inconclusive neuropsychological investigation

Abstract: The findings indicate that the outcome of on-road assessment is most related to cognitive skills such as attention and processing speed in combination with cognitive flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The on‐road test evaluation employed in the present study was similar to the procedure of Alexandersen et al . and Schanke and Sundet . Patients received no training in driving skills prior to the on‐road test.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…The on‐road test evaluation employed in the present study was similar to the procedure of Alexandersen et al . and Schanke and Sundet . Patients received no training in driving skills prior to the on‐road test.…”
Section: Methodssupporting
confidence: 84%
“…Tests designed to measure focused and divided attention, cognitive speed, visual−motor reaction time, working memory and perceptual abilities are shown to significantly predict on‐road driving performance, whereas tests designed to measure other abilities such as verbal functioning and verbal memory have shown less or no predictive power .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2 studies using DAT and control groups, 1 found a significant association [33] and the other not [40] . In a study on the effect of age, the DSST was the best predictor of driving under a single or visual double task [70] , and it was also one of the 3 significant predictive variables of ability to drive in drivers for whom a previous neuropsychological evaluation performed in a specialized setting did not make it possible to judge their fitness to drive [71] . Moreover, the DSST and Useful Field of View, a test consistently predicting a variety of driving outcomes among older and clinical populations [32,40,52,72,73] , showed similar trajectories of change over a 5-year period, and the authors suggested that both measures may reflect the same cognitive domain [74] .…”
Section: Discussionmentioning
confidence: 99%
“…A valid concern in this context then is the driving ability of CNCP patients on opioids. Driving is a complex task and requires integration of psychomotor function, visual-spatial abilities and cognitive skills [88]. Fishbain reviewed studies that assessed psychomotor function and driving ability in opioid dependent patients and found strong evidence for no impairment of psychomotor function and driving ability [89].…”
Section: Opioids and Functional Outcomesmentioning
confidence: 99%